Health Analysis of Acacia (Acacia crassicarpa) Seedling in the Nursery of PT. Sekato Pratama Makmur in Bukit Batu District, Bengkalis Regency, Riau Province - Dini Aulia R. Arsetia; Muhammad Mardhiansyah; Pebriandi Pebriandi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Acacia is a top priority plant in developing industrial forest plantations, especially in Sumatra, because it meets the requirements as raw material for the pulp and paper industry. PT. Sekato Pratama Makmur (SPM) is a company that cultivates this plant. Constraints often encountered in developing pulpwood plantations include pests, diseases, and seedlings that fail to adapt to the field. It is essential to analyze the health of acacia seedlings in the PT. SPM nursery, as a basis for pest and disease control and plant protection measures. This study aims to determine the intensity of pest and disease attacks and the health condition of acacia plants. Methodology: The scoring method used in this study was used to determine the attack score on acacia seedlings. Data from this study were analyzed descriptively and quantitatively using the formulas of survival rate, intensity of pest and disease attack, and percentage of health. Findings: The results showed that the percentage of pest and disease attack intensity was 1.90% in sowing 1, 6.16% in sowing 2, and 5.88% in sowing 3, with mild damage. The percentage of acacia plant health was 95.10% in sowing 1, 89.38% in sowing 2, and 89.20% in sowing 3. Damage to leaves included leaf curling, leaf holes, leaf yellowing, leaf spots, and blight. This indicates that the acacia seedlings in the nursery are in good condition. The low intensity and minor severity of pest and disease attacks demonstrate that the control measures implemented by PT. SPM are effective. Contribution: This research contributes to the development of effective pest control strategies by providing initial information on the health condition of acacia seedlings and supports the long-term success of field planting.